Hubungan Kelengkapan Resume Medis Rawat Inap BPJS Dengan Persetujuan Klaim BPJS Di RS Advent Medan 2024 - Christy, Johanna; Simanjuntak, Marta; Hutasoit, Theresia; Erlindai, Erlindai; Lase, Siji Valentine (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2026)
Minister of Health Regulation Number 269/MENKES/PER/III/2008, states that a discharge summary (resume) is carried out by a doctor or dentist on a patient. BPJS claims are submissions of costs incurred by BPJS participant patients from the hospital to BPJS Kesehatan, carried out every month and billed to BPJS Kesehatan. The purpose of this study was to determine the relationship between the completeness of the inpatient medical resume and the approval of BPJS claims at Medan Adventist Hospital. This study uses a quantitative descriptive research method with a cross-sectional research design where data collection was carried out through interviews and checklists carried out in June 2024. be concluded that most BPJS claim applications were not approved Based on the results of the study, the completeness of medical resumes in 50 incomplete and unapproved files amounted to 31 files with a percentage of 38% while those that were complete and approved amounted to 19 files with a percentage of 62%. From the results of the study, it can due to the large number of incomplete medical resumes. Suggestions for healthcare workers are required to understand and implement Standard Operating Procedures (SOPs) for completing medical resumes in accordance with applicable regulations, both hospital regulations and regulations contained in legislation. Improve healthcare workers' discipline in completing medical resumes by recording any missing components of the medical resume, then conducting a joint evaluation within a certain timeframe, especially for those directly involved in recording medical resumes and the BPJS claims section.